Quality of ‘Ubá’ mangos from harvest to receipt by the processing plant - Neves, Érica Granato Faria (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Currently, fruit is one of the most competitive segments of the Brazilian agricultural sector. Fresh fruit and its derivatives show an upward trend in exports. The sectors potential stems from an increase in consumption in both internal and external markets. The increasing consumption of fruits worldwide is one of the factors that signal favourable opportunities for Brazilian fruit growing. Brazil, which is the third largest fruit producer in the world behind China and India, has been gradually expanding its participation in the world trade of fresh fruits and derivatives (Vilela and Moreira, 2008)25. The region of Zona da Mata of Minas Gerais contains several factory, which prepare fruits produced in the region. Among the currently marketed fruit products, „Ubá? mangos are well accepted by processing plant because of their colour characteristics, flavour and texture and their acceptance by domestic and foreign markets (Ramos et al., 2005)22. The climate throughout much of the Zona da Mata of Minas Gerais is appropriate for the cultivation of mango trees that is it exhibits well-defined dry and rainy seasons. This climate has led to the region becoming an important producing centre for mangos, including organic fruits. During the period of floral differentiation and flowering, the climate exhibits dry, mild temperatures, while during the formation and filling phase of the fruits, the temperatures and precipitation increase, allowing a satisfactory production of fruits without the need for intensive cultivation.